The Effect of Financial Literature and Behavior on Individual Investment Decision Behavior - Mohamad Duddy Dinantara; Umi Narimawati; Azhar Affandi; Sidik Priadana; Heri Erlangga (International Journal of Education, Information Technology, and Others, 2022)
The purpose of this study was to determine the effect of financial literacy and financial behavior on the behavior of individual investment decisions in Perumnas Project Employees either partially or simultaneously. The method used is a quantitative method with a descriptive approach. The results of this study are financial literacy has a significant effect on individual investment decision behavior with the regression equation Y = 7.129 + 0.342X1. The correlation value of 0.633 means that the two variables have a strong relationship level. The value of determination or contribution of influence is 40.0%. Hypothesis test obtained t count > t table or (3,269 > 1,987). Thus H0 is rejected and H1 is accepted. This means that there is a significant influence between financial literacy on the behavior of individual investment decisions. Financial behavior has a significant effect on individual investment decision behavior with the regression equation Y = 9607 + 0.225X2. The correlation value of 0.383 means that the two variables have a strong relationship level. The value of determination or contribution of influence is 38.3%. Hypothesis test obtained t count > t table or (2,815 > 1,987). Thus H0 is rejected and H2 is accepted. This means that there is a significant influence between financial behavior on individual investment decision behavior. Financial literacy and financial behavior have a significant effect on individual investment decision behavior with the regression equation Y = 5.876 + 0.209X1 + 0.121X2. The correlation value is 0.671. This means that the independent variable with the dependent variable has a strong relationship level with a coefficient of determination of 45.0%. While the remaining 55% is influenced by other factors. Hypothesis test obtained value of F count > F table or (35,646 > 2,710). Thus H0 is rejected and H3 is accepted. This means that there is a simultaneous significant influence between financial literacy and financial behavior on individual investment decision behavior (Study of Perumnas Project Employees).